2021
DOI: 10.3389/fbioe.2021.674260
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor Suspension Culture: Differentiation and Production of Cardiomyocyte Spheroids From Human Induced Pluripotent Stem Cells

Abstract: Human induced-pluripotent stem cells (hiPSCs) can be efficiently differentiated into cardiomyocytes (hiPSC-CMs) via the GiWi method, which uses small-molecule inhibitors of glycogen synthase kinase (GSK) and tankyrase to first activate and then suppress Wnt signaling. However, this method is typically conducted in 6-well culture plates with two-dimensional (2D) cell sheets, and consequently, cannot be easily scaled to produce the large numbers of hiPSC-CMs needed for clinical applications. Cell suspensions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Apoptotic cells also tended to be located toward the center of C1 spheroids, which suggests that the vascular cells and CFs present in C4 spheroids facilitated access of the culture medium to the spheroid interior. These findings are consistent with previous work supporting the crucial role that non-myocytes play in promoting CM survival particularly where nutrient and oxygen diffusion is limited through release of paracrine factors (Ye et al, 2014;Hodgkinson et al, 2016;Giacomelli et al, 2017;Giacomelli et al, 2020;Munarin et al, 2020;Pretorius et al, 2021).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Apoptotic cells also tended to be located toward the center of C1 spheroids, which suggests that the vascular cells and CFs present in C4 spheroids facilitated access of the culture medium to the spheroid interior. These findings are consistent with previous work supporting the crucial role that non-myocytes play in promoting CM survival particularly where nutrient and oxygen diffusion is limited through release of paracrine factors (Ye et al, 2014;Hodgkinson et al, 2016;Giacomelli et al, 2017;Giacomelli et al, 2020;Munarin et al, 2020;Pretorius et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…The inclusion of hiPSC-ECs, -SMCs, and CFs in CM spheroids increased spheroid size and improved cell viability hiPSCs were differentiated into CMs, ECs, SMCs, and CFs via published protocols or the use of commercially available kits (Yang et al, 2016;Zhang et al, 2019;Kahn-Krell et al, 2021), and flow-cytometry analyses with lineage-specific antibodies [CMs: cardiac troponin T (cTnT), ECs: CD144 and CD31, SMCs: smooth-muscle actin (SMA), CFs: TE-7] confirmed that the purity of each differentiated cell population exceeded 95% (Supplementary Figures S1-S4). Spheroids containing CMs alone (C1) and spheroids containing a 4:2:1 ratio of CMs, ECs, and SMCs (C3) or a 4:2:1:1 ratio of CMs, ECs, SMCs, and CFs (C4) were produced by culturing the indicated proportions of cell types in low-attachment 96-well U plates for 1 week to promote aggregation and fusion (Figures 1A,B), and then in low-attachment 6-well plates on an orbital shaker for the remainder of the culture period (Figures 1C,D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations